2019
DOI: 10.1002/jcla.23105
|View full text |Cite
|
Sign up to set email alerts
|

Role of matrix metalloproteinase‐9 gene polymorphisms in glaucoma: A hospital‐based study in Chinese patients

Abstract: Background Glaucoma is the irreversible vision loss and contributes second leading cause of blindness worldwide. Matrix metalloproteinase‐9 (MMP‐9) is involved with remodeling and destruction of extracellular matrix. Elevated MMP‐9 levels and various functional variants of MMP‐9 have been associated with glaucoma in different population. In the current investigation, we tested association of MMP‐9 common variants with different clinical categories of glaucoma in Chinese population. Materials and Methods We enr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 24 publications
2
22
0
Order By: Relevance
“…Locus rs2250889 MMP9, which was determined in the present study as associated with XFG, was previously reported as a candidate for PACG [32,34]. Interestingly, that allele G of this locus was determined as a risk factor for both PACG and XFG (OR = 1.57-1.71).…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Locus rs2250889 MMP9, which was determined in the present study as associated with XFG, was previously reported as a candidate for PACG [32,34]. Interestingly, that allele G of this locus was determined as a risk factor for both PACG and XFG (OR = 1.57-1.71).…”
Section: Discussionsupporting
confidence: 53%
“…Interestingly, that allele G of this locus was determined as a risk factor for both PACG and XFG (OR = 1.57-1.71). On the other hand, no association of this variant with primary openangle glaucoma was determined [32].…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Due to their pleiotropism, polymorphisms of the MMP9 genes play a key role in multiple biological pathways and therefore have been implicated not only in peptic ulcer [ 13 , 73 , present study], but also in cardiovascular diseases [ 60 , 61 ] as well as a broad range of other disorders involving processes of synthesis and degradation of extracellular matrix: various cancers, including digestive [ 46 48 , 74 76 ], glaucoma [ 27 , 77 , 78 ], and others [ 79 82 ].…”
Section: Discussionmentioning
confidence: 99%
“…The dataset contains the raw data (supplementary Table), frequencies of alleles and genotypes ( Table 1 ) for three SNPs of two MMP genes (rs1799750 MMP1 , rs3918242 and rs17576 MMP9 ) in Russian patients diagnosed with POAG, EH, and PU. These polymorphisms were previously reported for their association with POAG, EH, and PU ( Table 2 ) [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] . The studied SNPs manifest the regulatory potential ( Table 3 ), which is evidenced by several eQTLs ( Table 4 ) and splicing QTLs ( Table 5 ).…”
Section: Data Descriptionmentioning
confidence: 87%